-3 - 1 = -4; -3 + 1 = -2
44 - 1 = 43; 44 + 1 = 45
-97 - 1 = -98; -97 + 1 = -96
-78 - 1 = -79; -78 + 1 = -77
56 - 1 = 55; 56 + 1 = 57
95 - 1 = 94; 95 + 1 = 96
50 - 1 = 49; 50 + 1 = 51
8 - 1 = 7; 8 + 1 = 9
36 - 1 = 35; 36 + 1 = 37
-89 - 1 = -90; -89 + 1 = -88
-83 - 1 = -84; -83 + 1 = -82
-37 - 1 = -38; -37 + 1 = -36
-14 - 1 = -15; -14 + 1 = -13
86 - 1 = 85; 86 + 1 = 87
2 - 1 = 1; 2 + 1 = 3
-18 - 1 = -19; -18 + 1 = -17
6 - 1 = 5; 6 + 1 = 7
76 - 1 = 75; 76 + 1 = 77
96 - 1 = 95; 96 + 1 = 97
84 - 1 = 83; 84 + 1 = 83